Diversité taxonomique des Hominidés fossiles en Asie : de nouvelles méthodes pour une vieille question - Stéphane Bouée; Florent Détroit (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The  objectives  of  this  study  were  to  determine  whether  the  fossils  discovered  in Asia  belong  to  one  or  several taxa, to identify them and to compare the distances between them to the distances between actual groups and species of anthropoids.For  this purpose, we have used new geometric morphometric methods. Twenty  three dimensional  landmarks were digitized on 110  skulls: 18  fossils  from Asia dated between 1,150,000  years and 6,000 BC, 31 modern Homo sapiens, 31 chimpanzees and 30 gorillas. Landmarks were registered by Generalized Procruste Analysis.We used a  logical and objective method with  three steps. 1) The  taxa variabilities were explored by using several distance  indices  (variance, Euclidean and Manhattan distances). 2) We have  chosen not  to arbitrarily group  fossils  in established taxonomic categories: Principal component analysis (PCA) and hierarchical classification methods (UPGMA and NJ) were applied  to  identify subgroups  for each of  the  four  taxa. Finally, Mahalanobis distances between  identified groups and subgroups were calculated and compared between each other.The  overall  variability  was  larger  for  the  fossil  group  than  for  any  of  the  three  actual  species,  although  the difference was statistically significant only for the comparison to the modern H. sapiens. Classification and PCA analysis identified two subgroups within the fossil group: one with an H. sapiens affinity and the other with an H. erectus affinity. The Mahalanobis distances were ordered as  follows  (decreasing order): gorilla/modern H. sapiens, chimpanzee/modern H. sapiens, chimpanzee/gorilla which was very similar to the distance between modern H. sapiens and H. erectus. This last distance was similar to the one between fossil H. sapiens and H. erectus. Distances between modern and fossil H. sapiens and between subgroups of actual species were similar and less than the preceding ones.We finally concluded that the fossils belong to two different taxa. The first (fossil H. sapiens) belongs to the same taxon as modern H. sapiens and the second, H. erectus, is different.